Manfaat Rehabilitasi Psikososial dalam Mendukung Pemulihan Orang dengan Gangguan Jiwa - Kartikasari, Ida Ayu; Hamid, Achir Yani S.; Hargiana, Giur (Journal of Telenursing (JOTING), 2024)
This research aims to analyze the benefits of psychosocial rehabilitation in supporting the recovery of people with mental disorders. The research method used was a literature review where article searches were carried out on the ProQuest, SpringerLink and EBSCOhost databases with publication years 2019-2023. The research results show that psychosocial rehabilitation has been proven to have a positive impact on the recovery of people with mental disorders. The positive impacts include: improving health behavior, improving functioning as an individual and increasing the ability to live independently and productively. Through psychosocial rehabilitation, people with mental disorders are able to increase their self-efficacy and satisfaction with their lives, which has a positive correlation in improving their quality of life. In conclusion, psychosocial rehabilitation is a program that must be integrated into the recovery of people with mental disorders. Keywords: People with Mental Disorders, Recovery, Psychosocial Rehabilitation